A comparative study of Islamic banking growth in Malaysia and Bahrain: a consideration of COVID-19 pandemic / Fatin Nur Liyana Mohamad Shahril ... [et al.] - Mohamad Shahril, Fatin Nur Liyana; Din, Ibtisam Athirah; Ahmad, Wahida; Amran, Nur Hazimah (Universiti Teknologi MARA, Perlis, 2024)
This study examines the factors influencing Islamic banking growth in Malaysia and Bahrain, key components of the broader Islamic finance industry crucial for economic development. Focusing on 14 Islamic banks in Malaysia and 10 in Bahrain over a 10-year period, the research investigates the impact of liquidity, profitability, asset quality, and capital on Islamic banking growth. Three models are introduced, pooling data for both countries and separately analysing Malaysia and Bahrain. The study introduces three models: 1) Model A, which pools all Malaysian and Bahrain Islamic banks; ii) Model B, which represents Islamic banks in Malaysia; and iii) Model C, which represents Bahraini Islamic banks. Newey-West regression is being used for Models A and B, while Pooled Ordinary Leased Square (POLS) is being utilized for Model C. The study reveals that Bahrain's Islamic banking growth surpasses Malaysia's. There are different drivers that influence the growth in each country. Asset quality and capital are significantly influencing the growth of both Malaysian and Bahraini Islamic banks, while Malaysian Islamic banking growth is significantly influenced by profitability. Additionally, liquidity is significantly influencing the growth of Bahraini Islamic banks. However, the growth of Islamic banking does not significantly differ during a crisis or non-crisis period for each country. These findings underscore the necessity for tailored approaches in both nations to enhance Islamic banking growth, contributing to the broader development of Islamic finance.